2006
DOI: 10.1007/bf03173577
|View full text |Cite
|
Sign up to set email alerts
|

An extention of the school moral atmosphere construct, and its association with aggressive behaviours in secondary school

Abstract: The first aim of this research is to introduce and to validate the new concept of School Normative Context, that revisits the concept of School Moral Atmosphere studied by Brugman and his colleagues through the SMAQ (1999) and validated also in the Italian context (Mancini & Fruggeri, 2005). The School Normative Context entails two new aspects: The first one concerns the interactive dimension of each specific school context and the second one concerns the perception of responsibility (internal vs. external) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Several studies have found a relation between moral atmosphere and antisocial behavior, both in the context of organized youth sport (e.g., Guivernau & Duda, 2002; Stephens, 2000), and in the context of the school (e.g., Brugman, Heymans, Boom, Karabanova, & Idobaeva, 2003; Høst et al., 1998; Mancini, Fruggeri, & Panari, 2006). The current study showed no significant multi‐variate association between moral atmosphere and antisocial behavior, but only a bivariate association.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found a relation between moral atmosphere and antisocial behavior, both in the context of organized youth sport (e.g., Guivernau & Duda, 2002; Stephens, 2000), and in the context of the school (e.g., Brugman, Heymans, Boom, Karabanova, & Idobaeva, 2003; Høst et al., 1998; Mancini, Fruggeri, & Panari, 2006). The current study showed no significant multi‐variate association between moral atmosphere and antisocial behavior, but only a bivariate association.…”
Section: Discussionmentioning
confidence: 99%